Florida Invader: African Python - Steve A. Johnson; Monica E. McGarrity (EDIS)
WEC287, a 2-page illustrated fact sheet by Steve Johnson and Monica McGarrity, is part of the Florida Invaders series. It provides key information and illustrations for identifying and reporting sightings of this large nocturnal predator that is native to sub-Saharan Africa but may be breeding in Florida. Published by the UF Department of Wildlife Ecology and Conservation, September 2010.